2002
DOI: 10.1159/000049896
|View full text |Cite
|
Sign up to set email alerts
|

P2X<sub>7</sub> Receptors Are Expressed during Mouse Nephrogenesis and in Collecting Duct Cysts of the <i>cpk/cpk</i> Mouse

Abstract: Background: Purinergic receptors are cell-surface molecules that bind extracellular nucleotides, notably ATP. The P2X family includes seven nonselective ion channels with one member, P2X7, implicated in cytolytic pore formation and cell death. Materials and Methods: We sought P2X7 expression in mouse nephrogenesis and cpk/cpk renal cyst growth, conditions in which both proliferation and apoptosis are prominent. Results: P2X7 immunolocalized to condensed metanephric mesenchyme: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Previous reports have shown that, in healthy mice, P2X7 is expressed in the renal collecting duct but not in the glomeruli or other tubules [62]. The function of P2X7 in collecting duct remains poorly understood.…”
Section: Discussionmentioning
confidence: 95%
“…Previous reports have shown that, in healthy mice, P2X7 is expressed in the renal collecting duct but not in the glomeruli or other tubules [62]. The function of P2X7 in collecting duct remains poorly understood.…”
Section: Discussionmentioning
confidence: 95%
“…This is not surprising given their past tutelage in the Burnstock group. They have led the field in determining that P2X 7 expression emerges in apoptotic and/ or diseased renal epithelial, interstitial, and glomerular cells, which is well documented by several groups [86,96,[98][99][100]. In particular, emergence of abundant P2X 7 expression has been documented in mouse models and in human cells and tissues within autosomal recessive (ARPKD) and autosomal dominant (ADPKD) polycystic kidney disease [96,[98][99][100].…”
Section: Nucleotide and Nucleoside Receptor Expression Along The Nephronmentioning
confidence: 99%
“…They have led the field in determining that P2X 7 expression emerges in apoptotic and/ or diseased renal epithelial, interstitial, and glomerular cells, which is well documented by several groups [86,96,[98][99][100]. In particular, emergence of abundant P2X 7 expression has been documented in mouse models and in human cells and tissues within autosomal recessive (ARPKD) and autosomal dominant (ADPKD) polycystic kidney disease [96,[98][99][100]. In diabetic and hypertensive rats, P2X 7 expression emerged and was abundant in multiple vascular and nonvascular cell types of the glomerulus [96,[98][99][100].…”
Section: Nucleotide and Nucleoside Receptor Expression Along The Nephronmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that purinergic signaling plays an important role in cystogenesis during both ADPKD and ARPKD 31,32 . Cyst cells of PCK rats have previously been shown to exhibit low basal [Ca 2+ ] i and loss of flow-mediated [Ca 2+ ] i signaling compared to healthy non-dilated collecting ducts of SD rats 13 .…”
Section: Representative Resultsmentioning
confidence: 99%